Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Stocking density effects on growth and physiological responses of pikeperch (Sander lucioperca) reared in in-pond raceways - Václav Kučera; Oleksandr Malinovskyi; Jitka Kolářová; Josef Velíšek; Tomáš Pěnka; Jiří Křišťan; Laura Ostolaza Perez-Cruz; Muhammad Nauman; Tomáš Policar (Aquaculture, 2027)

Influence of hydrogen blending on the heat transfer characteristics of premixed methane/air jet impinging flame - Feiyang Li; Jianfeng Pan; Zhongjia Li; Yuejin Zhu; Muhammad Nauman; Wenming Yang (Fuel, 2026)

Seismic and petrophysical evaluation of the Paleocene Lockhart Formation as a fractured carbonate reservoir in the upper Indus Basin, Pakistan - Muhammad Nauman Ejaz; Hua-Wei Zhou; Zohaib Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Comparative study on the implementation of Custom Convolutional Neural Networks (CNNs), MobileNet V3 and ResNet-50 architecture for defect detection in Carbon Fiber Reinforced Plastics (CFRPs) - Hussnain Abid; Muhammad Daniyal Hassan; Saad Nauman (Next Research, 2026)

Nonlinear water wave dynamics of data-driven soliton solutions for the Kakutani–Matsuuchi model in Ocean Engineering - Muhammad Qasim; Tahir Shahzad; Fengping Yao; Muhammad Zafarullah Baber; Nauman Ahmed (Ocean Engineering, 2026)

Exploring Carissa spinarum as a therapeutic candidate: metabolite profiling and antimicrobial evaluation - Laiba Ali; Shahid Nawaz; Sikandar Ali; Asad Ur Rehman; Iram Liaqat; Shaukat Ali; Muhammad Nauman Aftab (Natural Product Research, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Biochemical and computational characterization of a recombinant catalase from Kocuria rhizophila for degradation of hydrogen peroxide in textile wastewater - Asma Zafar; Hira Mubeen; Sadaf Hameed; Mahjabeen Khan; Hafsa Sohail; Maheen Zaka; Muhammad Nauman Aftab; Anuga Liyanage (Antonie van Leeuwenhoek, 2026)

Overcoming cellular secretion bottlenecks: advanced secretion engineering and molecular tailoring for next-generation microbial α-amylases with enhanced industrial performance - Saleem Ahmad; Muhammad Nauman Aftab; Muhammad Ghalib; Muhammad Shahbaz Aslam (World Journal of Microbiology and Biotechnology, 2026)

A Critical Review on Advance Molecular Distortion Techniques for Textile Wastewater Treatment in Pakistan - Sahrish Ashraf; Muhammad Sultan; Muhammad Wakil Shahzad; Muhammad Imran; Rana M. A. Kanwar; Muhammad Nauman Ashraf; Zahid Mahmood Khan; Zubair Khaliq; Muhammad Bilal Qadir (Water, Air, & Soil Pollution, 2026)

Evaluation of the antibacterial activity of Ag NPs, TiO2 NPs, and ZnO NPs against wastewater-derived multidrug-resistant bacteria - Sakina Mustafa; Alia Mustafa; Qamar Abbas; Muhammad Nauman Zahid (Toxicology and Environmental Health Sciences, 2026)

Recent advances in machine/deep learning frameworks for biochar application in soil amendment and remediation - Muhammad Waqas; Mohsin Nawaz; Rongli Yang; Waseem Tariq; Muhammad Nauman Tahir; Shakeel Ahmad (Applied Soil Ecology, 2026)

Variable Rate Irrigation Through Digital Agriculture for Sustainable Water Management: A Meta Review on Current Challenges and Future Directions - Nauman Yaqoob; Aitazaz A. Farooque; Syed Hamid Hussain Shah; Farhat Abbas; Muhammad Hassan (Water Resources Management, 2026)
Efficient agricultural water management is essential due to increasing pressure on global water resources. To support environmentally sustainable farming water management, a detailed review of existing research on data-driven irrigation systems is conducted. The review paper reviews present advancements, challenges, and future directions based on extensive peer-reviewed studies on variable-rate irrigation (VRI), machine learning and artificial intelligence (AI), deep learning techniques, smart sensing technologies, state-of-the-art control systems, and coupled frameworks. To ensure transparency and reproducibility, studies were selected through a systematic search of major research databases (such as Dimensions AI, Web of Science, and Scopus) using key keywords. The inclusion criteria required that studies be peer-reviewed, published in English between 2000 and 2023, and specifically address precision irrigation techniques, control strategies, or implementation methods relevant to VRI. Conference proceedings and high-impact journal articles were prioritized. This review focuses on three central components of precision irrigation: (1) development of prescription maps, (2) innovative control strategies, and (3) realistic implementation of VRI systems. To improve the efficiency and flexibility of modern irrigation systems, the paper identifies emerging knowledge gaps and proposes innovative pathways to address them. The study describes a new methodology through a case study on developing irrigation prescription maps. Precision irrigation, especially when supported by VRI and state-of-the-art AI technologies, has shown considerable potential to improve water productivity. This approach assists researchers, practitioners, and stakeholders in designing, comparing, and executing sustainable irrigation strategies.

Omics-driven soil bioremediation of emerging contaminants: Integrating sensors, digital twins, and microbial biotechnology - Asad Shah; Mohammad Nauman Khan; Waqar Ali; Muhammad Numan Khan; Hidayat Ullah; Zahra Barati; Adil Farooq Lodhi; Lixiao Nie (Applied Soil Ecology, 2026)

Advances in Understanding Cold Tolerance Mechanisms in Potato (Solanum Tuberosum L.): Physiological, Biochemical, Molecular, and Breeding Perspectives - Barkat Ali; Wajid Anwar; Muhammad Nauman Khan (American Journal of Potato Research, 2026)

Thermochemical distribution and emission characteristics of CH4/air premixed laminar flames with wall effects under varying ammonia ratios - Zhongjia Li; Jianfeng Pan; Feiyang Li; Muhammad Nauman; Wenming Yang (Fuel, 2026)

Hematological, Histological, and NMR Analysis of Meat Quality and Growth Performance of Broilers Fed with Probiotics Bacillus licheniformis-Supplemented Poultry Feed - Basit Ali Khan; Sundas Sharif; Amna Mehdi; Iram Liaqat; Sikander Ali; Asad-ur-Rehman; Liangcai Peng; Sohail Afzal; Muhammad Nauman Aftab (Probiotics and Antimicrobial Proteins, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Bovine mastitis and antimicrobial resistance in Pakistan’s dairy sector: current status and future prospects - Nauman Zaheer Ghumman; Mieghan Bruce; Amanda Duarte Barbosa; Muhammad Ijaz; Jiaxin Peng; Jully Gogoi-Tiwari (Veterinary Research Communications, 2026)
Bovine mastitis remains one of the most widespread and economically significant diseases affecting the dairy sector in Pakistan. Despite being a leading global milk producer, Pakistan’s dairy industry faces persistent challenges in controlling mastitis, particularly among smallholder farmers with limited access to veterinary care and diagnostic tools. Antibiotics are frequently used to manage mastitis, often without veterinary oversight, contributing to the growing concern of antimicrobial resistance (AMR). The widespread presence of Staphylococcus aureus , a biofilm-forming pathogen, further complicates treatment and accelerates resistance development. Pakistan has initiated efforts to address AMR through national action plans. However, gaps remain in surveillance, responsible antibiotic use, and access to affordable alternatives. This review examines the current landscape of bovine mastitis in Pakistan, including its epidemiology, economic impact, therapeutic practices, and AMR trends. It also outlines practical, low-cost recommendations for improving mastitis management and reducing inappropriate use of antibiotics, particularly in rural settings. Addressing these interconnected challenges through locally adapted, sustainable approaches is essential for improving animal health, milk safety, and long-term productivity in Pakistan’s dairy sector, whilst addressing the global challenge of AMR.

Thermal and chemical analysis on the hydrogen heterogeneous reaction characteristics in a catalytic micro-combustor with blunt body - Qingbo Lu; Shijia Ding; Yi Zhang; Yunchao Wang; Baowei Fan; Muhammad Nauman; Wenming Yang; Jianfeng Pan (Fuel, 2026)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Soil Pollution in Urban Environments: Sources, Consequences, Potential Mitigation Strategies and the Importance of Sustainable Urban Development - Muhammad Nauman Hanif; Ian Bartican Benitez (Water, Air, & Soil Pollution, 2025)

Climate mitigation through urban forests: ecosystem services and species diversity in Rimba Ilmu, Universiti Malaya, Malaysia - Nur Hanisah Rahim; Sarah Abdul Razak; Chng Saun Fong; Chang Xue; Khairunnisa Hasikin; Fatchur Rohman; Siti Nasuha Hamzah; Tabassum Yaseen; Alevcan Kaplan; Muhammad Nauman Khan; Sezai Ercisli (Genetic Resources and Crop Evolution, 2025)

Effect of inclined wall on heat transfer and emission characteristics of methane/ammonia/air premixed jet flame - Chun Zeng; Jianfeng Pan; Baowei Fan; Chao Jiang; Feiyang Li; Muhammad Nauman; Wenming Yang (Fuel, 2025)

Effect of Ocimum tenuiflorum L. compounds on Oreochromis mossambicus: a combination of molecular docking, biochemical dynamics, and antifertility assessment - Sajida Afzal; Siraj Khan; Muhammad Nauman Khan; Zahida Nasreen; Hansa Gul; Mian Inam Zaib; Hameed Alsamadany; Khalid H. Alamer; Ibtisam M. Alsudays; Muhammad Tahir Naseem (Aquaculture International, 2025)

Bifurcation analysis and turing instability of the ecological model having Beddington–Deangelis-type functional response - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Fengping Yao (Modeling Earth Systems and Environment, 2025)

Effects of chlorophenols on microbial activity and functional diversity: Recent advances in OMICs approaches and soil microbial remediation - Nadeem Iqbal; Muhammad Nauman; Babar Hussain; Sami Ullah; Palanisamy Vasudhevan; Dil Khurram; Riyazuddin Riyazuddin; Shengyan Pu (Applied Soil Ecology, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

Exploring the fixed point theory and numerical modeling of fish harvesting system with Allee effect - Muhammad Waqas Yasin; Mobeen Akhtar; Nauman Ahmed; Ali Akgül; Qasem Al-Mdallal (Modeling Earth Systems and Environment, 2025)

High-Sensitivity RT-LAMP Assay Enables Rapid, Field-Deployable Detection of Candidatus Liberibacter Asiaticus in Crude DNA Extracts from Citrus Phyllosphere and Psyllid Vectors - Ummad ud Din Umar; Syed Muhammad Zaka; Muhammad Nauman Tahir; Muhammad Kashif; Ateeq Ur Rehman; Sagheer Atta; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Spatio-temporal patterns and Turing–Hopf bifurcation in a spatially extended prey–predator model with ratio-dependent interactions - Muhammad Waqas Yasin; Nauman Ahmed; Ali Akgül; Muhammad Zafarullah Baber; Dumitru Baleanu; Ovidiu Tintareanu-Mircea (Modeling Earth Systems and Environment, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

Eco-friendly herbicide tolerance in maize (Zea mays Linn.) using moringa (Moringa oleifera Lam.) leaf extract - Hameed Ullah Khan; Muhammad Mudasar Aslam; Tahir Iqbal; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Muhammad Nauman Khan; Majid Iqbal; Alevcan Kaplan; Sarah Abdul Razak; Baber Ali; Muhammad Siddique Afridi; et al. (Acta Physiologiae Plantarum, 2025)

Magnetic attraction constructed photoelectrocatalytic anode to enhance the simultaneous degradation of 17α-ethinylestradiol and tetracycline in reclaimed water - Huan He; Jingxian Mei; Feng Liu; Yu Yan; Muhammad Nauman Tahir; Gui Yang; Ziwei Guo; Guoli Dong; Juhong Zhan; Bin Huang; Xuejun Pan (Journal of Water Process Engineering, 2025)

Residual effects of biochar and nano-modified biochar on growth and physiology under saline environment in two different genotype of Oryza sativa L. - Haider Sultan; Hafiz Muhammad Mazhar Abbas; Mohammad Faizan; Abolghassem Emamverdian; Asad Shah; Saraj Bahadur; Yusheng Li; Mohammad Nauman Khan; Lixiao Nie (Journal of Environmental Management, 2025)

Spore morphometric analysis in Sino-Himalayan and W-Himalayan Athyriaceae taxa: taxonomic insights and molecular phylogenetic comparison - Syed Nasar Shah; Mushtaq Ahmad; Mohammad Javed Ansari; Muhammad Nauman Khan; Majid Iqbal; Baber Ali; Sami Al Obaid (Genetic Resources and Crop Evolution, 2025)

An in-depth investigation of the nutraceutical value and medicinal perspectives of wild medicinal plants in Ojhor Valley, Hindukush Range, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Sana Wahab; Baber Ali; Sami Al Obaid; Mohammad Javed Ansari (Genetic Resources and Crop Evolution, 2025)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

Breeding for water-use efficiency in wheat: progress, challenges and prospects - Aqsa Hafeez; Shehzad Ali; Muhammad Ammar Javed; Rashid Iqbal; Muhammad Nauman Khan; Fatih ÇIĞ; Ayman EL Sabagh; Turki Abujamel; Steve Harakeh; Sezai Ercisli; Baber Ali (Molecular Biology Reports, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Sustainable development goals and green human resource management: A comprehensive review of environmental performance - Abdul Haseeb Tahir; Muhammad Umer; Shazia Nauman; Kashif Abbass; Huaming Song (Journal of Environmental Management, 2024)

Mathematical modeling of Ebola using delay differential equations - Ali Raza; Nauman Ahmed; Muhammad Rafiq; Ali Akgül; Alicia Cordero; Juan R. Torregrosa (Modeling Earth Systems and Environment, 2024)
Nonlinear delay differential equations (NDDEs) are essential in mathematical epidemiology, computational mathematics, sciences, etc. In this research paper, we have presented a delayed mathematical model of the Ebola virus to analyze its transmission dynamics in the human population. The delayed Ebola model is based on the four human compartments susceptible, exposed, infected, and recovered (SEIR). A time-delayed technique is used to slow down the dynamics of the host population. Two significant stages are analyzed in the said model: Ebola-free equilibrium (EFE) and Ebola-existing equilibrium (EEE). Also, the reproduction number of a model with the sensitivity of parameters is studied. Furthermore, the local asymptotical stability (LAS) and global asymptotical stability (GAS) around the two stages are studied rigorously using the Jacobian matrix Routh–Hurwitz criterion strategies for stability and Lyapunov function stability. The delay effect has been observed in the model in inverse relation of susceptible and infected humans (it means the increase of delay tactics that the susceptibility of humans increases and the infectivity of humans decreases eventually approaches zero which means that Ebola has been controlled into the population). For the numerical results, the Euler method is designed for the system of delay differential equations (DDEs) to verify the results with an analytical model analysis.

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Quantitative and qualitative approach for accessing and predicting food safety using various web-based tools - Hafiz Muhammad Rizwan Abid; Nimrah Khan; Athar Hussain; Zainab Bintay Anis; Muhammad Nadeem; Nauman Khalid (Food Control, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Navigating sustainable horizons: exploring the dynamics of financial stability, green growth, renewable energy, technological innovation, financial inclusion, and soft infrastructure in shaping sustainable development - Muhammad Nauman; Rehana Naheed; Junaid Khan (Environmental Science and Pollution Research, 2024)

Biochar and nano biochar: Enhancing salt resilience in plants and soil while mitigating greenhouse gas emissions: A comprehensive review - Haider Sultan; Yusheng Li; Waqas Ahmed; Mu yixue; Asad Shah; Mohammad Faizan; Aqeel Ahmad; Hafiz Muhammad Mazhar Abbas; Lixiao Nie; Mohammad Nauman Khan (Journal of Environmental Management, 2024)

Recent advances in applications of marine hydrocolloids for improving bread quality - Anum Ishaq; Muhammad Nadeem; Rafiq Ahmad; Zahoor Ahmed; Nauman Khalid (Food Hydrocolloids, 2024)

Numerical study on hydrogen heterogeneous reaction characteristic in a micro catalytic combustor with blunt body - Qingbo Lu; Qiongyao Wang; Baowei Fan; Yi Zhang; Yu Wang; Muhammad Nauman; Jianfeng Pan (Fuel, 2024)

Recent trends in hydrogen-associated treatments for maintaining the postharvest quality of fresh and fresh-cut fruits and vegetables: A review - Maratab Ali; Sara Batool; Nauman Khalid; Sajid Ali; Muhammad Ammar Raza; Xiaoan Li; Fujun Li; Zhang Xinhua (Food Control, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Global insights into micro-macro mechanisms and environmental implications of limestone calcined clay cement (LC3) for sustainable construction applications - Nauman Ijaz; Wei-Min Ye; Zia ur Rehman; Zain Ijaz; Muhammad Faisal Junaid (Science of The Total Environment, 2024)

Experimental and numerical study of an innovative twined tube HX design - Muhammad Ali Khan; Muhammad Daniyal Khalid; Muhammad Ilyas; Muhammad Daniyal Nauman; Muhammad Asim; Khalid Waheed; Fatih Aydogan (Annals of Nuclear Energy, 2024)

Phytotoxic Responses and Plant Tolerance Mechanisms to Cadmium Toxicity - Nijara Baruah; Nirmali Gogoi; Swarnendu Roy; Palakshi Bora; Juri Chetia; Noreen Zahra; Nauman Ali; Parikshit Gogoi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Geospatial modeling of heterogeneous geotechnical data using conventional and enhanced conception of modified Shepard method-based IDW algorithms: application and appraisal - Zain Ijaz; Cheng Zhao; Nauman Ijaz; Zia ur Rehman; Aashan Ijaz; Muhammad Faisal Junaid (Bulletin of Engineering Geology and the Environment, 2023)

Effects of different fat replacers on functional and rheological properties of low-fat mozzarella cheeses: A review - Aqsa Akhtar; Iqra Nasim; Muhammad Saeed ud Din; Tetsuya Araki; Nauman Khalid (Trends in Food Science & Technology, 2023)

Improving bio aviation fuel yield from biogenic carbon sources through electrolysis assisted chemical looping gasification - Mohammad Shahrivar; Muhammad Nauman Saeed; Gajanan Dattarao Surywanshi; Tobias Mattisson; Amir H. Soleimanisalim (Fuel, 2023)

Development of a new base isolation system using the concept of metamaterials - Muhammad Nauman Masoom; Qurat ul Ain Karim; Irtaza Badar; Rao Arsalan Khushnood; Fawad Ahmed Najam; Ahmer Naseer (Engineering Structures, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Engineering of oxygen vacancy defect in CeO2 through Mn doping for toluene catalytic oxidation at low temperature - Ahmed Ismail; Muhammad Zahid; Sharafat Ali; Syed ul Hasnain Bakhtiar; Nauman Ali; Adnan Khan; Yujun Zhu (Environmental Research, 2023)

Integrating wheat straw and silica fume as a balanced mechanical ameliorator for expansive soil: a novel agri-industrial waste solution - Usama Khalid; Zia ur Rehman; Nauman Ijaz; Inamullah Khan; Muhammad Faisal Junaid (Environmental Science and Pollution Research, 2023)

BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws - Chengbao Xu; Tao Xia; Hao Peng; Peng Liu; Yihong Wang; Yanting Wang; Heng Kang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Bioremediation of heavy metals polluted environment and decolourization of black liquor using microbial biofilms - Iram Liaqat; Noor Muhammad; Chaman Ara; Uzma Hanif; Saiqa Andleeb; Muhammad Arshad; Muhammad Nauman Aftab; Chand Raza; Muhammad Mubin (Molecular Biology Reports, 2023)

Remediation methods of heavy metal contaminated soils from environmental and geotechnical standpoints - Zia ur Rehman; Muhammad Faisal Junaid; Nauman Ijaz; Usama Khalid; Zain Ijaz (Science of The Total Environment, 2023)

Production of fuel oil from elastomer rubber waste via methanothermal liquefaction - Nabeel Ahmad; Nauman Ahmad; Usama Ahmed; Abdul Gani Abdul Jameel; Um-e-Salma Amjad; Murid Hussain; Muhammad Maaz Arif (Fuel, 2023)

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

Deep reinforcement learning-based long-range autonomous valet parking for smart cities - Muhammad Khalid; Liang Wang; Kezhi Wang; Nauman Aslam; Cunhua Pan; Yue Cao (Sustainable Cities and Society, 2023)

An assessment of the efficacy of biochar and zero-valent iron nanoparticles in reducing lead toxicity in wheat (Triticum aestivum L.). - Muhammad Nauman Mahamood; Sihang Zhu; Ali Noman; Abid Mahmood; Sana Ashraf; Muhammad Aqeel; Muhammad Ibrahim; Sobia Ashraf; Rock Keey Liew; Su Shiung Lam; Muhammad Kashif Irshad (Environmental Pollution, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Strengthening potential of xanthan gum biopolymer in stabilizing weak subgrade soil - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Zain Ijaz; Zia ur Rehman (Clean Technologies and Environmental Policy, 2022)

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

Microwave-Assisted Physically Cross-Linked Chitosan-Sodium Alginate Hydrogel Membrane Doped with Curcumin as a Novel Wound Healing Platform - Hassan A. Albarqi; Abdulsalam A. Alqahtani; Irfan Ullah; Nauman Rahim Khan; Hafiz Muhammad Basit; Tayyaba Iftikhar; Abdul Wahab; Muhammad Ali; Muhammad Badar (AAPS PharmSciTech, 2022)

Value addition and risk assessment of dairy digestate as biofertilizer on crop yield and soil fertility - Sidra Mukhtar; Abdullah Yasar; Yusra Mahfooz; Rizwan Rasheed; Amtul Bari Tabinda; Muhammad Adnan Ashraf; Muhammad Nauman; Afifa Malik (Arabian Journal of Geosciences, 2022)

Economic assessment of water-saving irrigation management techniques and continuous flooded irrigation in different rice production systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Fahimuddin Shah; Shakeel Ahmad Anjum; Muhammad Farooq (Paddy and Water Environment, 2022)

Role of modified diet and gut microbiota in metabolic endotoxemia in mice - Iram Liaqat; Arjumand Iqbal Durrani; Urooj Zafar; Saima Rubab; Mehwish Faheem; Muhammad Mubin; Chand Raza; Nauman Aftab (Archives of Microbiology, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

Influence of Nitrogen Fertilization Pattern on Productivity, Nitrogen Use Efficiencies, and Profitability in Different Rice Production Systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Khawar Jabran; Mohsin Nawaz; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

High intrinsic seed Zn concentration improves abiotic stress tolerance in wheat - Muhammad Faran; Muhammad Farooq; Abdul Rehman; Ahmad Nawaz; Muhammad Kamran Saleem; Nauman Ali; Kadambot H. M. Siddique (Plant and Soil, 2019)

Morpho-physiological and biochemical responses of tolerant and sensitive rapeseed cultivars to drought stress during early seedling growth stage - Mohammad Nauman Khan; Jing Zhang; Tao Luo; Jiahuan Liu; Fei Ni; Muhammad Rizwan; Shah Fahad; Liyong Hu (Acta Physiologiae Plantarum, 2019)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Comparative studies of three novel freshwater microalgae strains for synthesis of silver nanoparticles: insights of characterization, antibacterial, cytotoxicity and antiviral activities - Muneeba Khalid; Nauman Khalid; Iftikhar Ahmed; Rumeza Hanif; Muhammad Ismail; Hussnain Ahmed Janjua (Journal of Applied Phycology, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Onion: Nature Protection Against Physiological Threats - Hafiz Ansar Rasul Suleria; Masood Sadiq Butt; Faqir Muhammad Anjum; Farhan Saeed; Nauman Khalid (Critical Reviews in Food Science and Nutrition, 2015)

A Question Mark on Iron Deficiency in 185 Million People of Pakistan: Its Outcomes and Prevention - Anwaar Ahmed; Asif Ahmad; Nauman Khalid; Angel David; Mansoor Abdullah Sandhu; Muhammad Atif Randhawa; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2014)

Erratum to: Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

Sphingobacterium pakistanensis sp. nov., a novel plant growth promoting rhizobacteria isolated from rhizosphere of Vigna mungo - Iftikhar Ahmed; Muhammad Ehsan; Yeseul Sin; Jayoung Paek; Nauman Khalid; Rifat Hayat; Young H. Chang (Antonie van Leeuwenhoek, 2014)

A Question Mark on Zinc Deficiency in 185 Million People in Pakistan—Possible Way Out - Nauman Khalid; Anwaar Ahmed; Muhammad Shahbaz Bhatti; Muhammad Atif Randhawa; Asif Ahmad; Rabab Rafaqat (Critical Reviews in Food Science and Nutrition, 2014)